Venture mania in Europe: Its causes and consequences - Andrea Schertler; Michael Stolpe (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
Over the course of the past twenty years, venture capital has fuelled an entrepreneurial revolution - first in the United States and now in Europe's common market -, which has opened new opportunities for technological innovation, capital investment and employment growth. Some of the most promising opportunities are in science-based industries, like software and biotechnology, which are often seen as driving the transformation to an increasingly knowledge- based economy. Indeed, this transformation would hardly be conceivable without the innovative contributions of business start-ups that rely on venture capital to finance their early stages of growth. So what, if anything, should governments do to support venture capital and help this transformation along? This paper will argue that governments must understand that venture capital is necessarily linked to specialization and therefore cannot be expected to play the same role in any two economies whose place, and contribution, within the international division of labour differ.
Keywords: 330; Unternehmensgründung; Innovation; Risikokapital; Arbeitsteilung; Internationale Arbeitsteilung; Hochtechnologiesektor; Finanzierungstheorie; Asymmetrische Information; Prestige; Wertpapieremission; Wettbewerb; Lernprozess; Subvention; Gewerbepolitik; Westeuropa; Großbritannien; Niederlande; Deutschland; USA